KEDUDUKAN PEREMPUAN DALAM ISLAM - Yusrul Hana, Muhamad (Sekolah Tinggi Agama Islam Program Studi Sejarah dan Kebudayaan Islam, 2022)
This paper describes the condition of women in Islam. The condition of women in the jahiliyyah period is very worrying. The position of women is greatly despised by men in every clan. They are considered weak humans who can bring disgrace to the family if a clan loses a war. Some clans even kill baby girls to avoid this misfortune. After Islam was brought by the Prophet Muhammad SAW came, the position of women began to be equalized with men. Although men should lead women because of their physical and psychological advantages. In this position, women are textually under the protection of men. However, in their careers and social activities, women have found their freedom since Islam came. The discussion that will be studied in this study includes several important things. First, is the condition of women during the jahiliyyah period. Second, the condition of women after the arrival of Islam brought by the Prophet Muhammad. The method used in this study is a historical research method including heuristics, criticism, interpretation, and historiography.